Studi Kasus Keterlambatan Motorik Kasar Anak Tunadaksa: - Novila Kurniawati; Risbon Sianturi; Heri Yusuf Muslihin (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2022)
This research is motivated by the lack of gross motor skills in early childhood with special needs (5-6 years) in PAUD Al-Istianah Tasikmalaya Regency. The purpose of this study is to find out the types of delays in grass motor development in early childhood, the causes of delays in childhood development, and solutions and handling from parents and teachers to delays in gross motor development in early childhood. The research method used is a qualitatuve approach with a case study method. This research was conducted in PAUD Al-Istianah, Tasikmalaya Regency with the subject og this study, namely a 6-year-old boy. Data collection techniques carried out by researchers are interviews, obervation, and documentation. The results of this study stated that the subjects studied experienced dealys in gross motor development in the muscles of hands and feet caused by neurological disorders that nad been sufferes since birth. The subject experienced the disorder because the subject was born prematurely, and the dealy was seen when the subject was 3 year.